An integrated care pathway for optimizing the investigation and management of pediatric pleural empyema - Paize, Fauzia; White, Elvina; Heaf, Louisa J.; Baillie, Colin; Kenny, Simon; Couriel, Jonathan M.; Heaf, David P.; Smyth, Rosalind; Southern, Kevin W. (Journal of Pediatric Infectious Diseases, 2007)
There are no reports of the use of an integrated care pathway (ICP) to facilitate the management of pleural empyema in children. Our aim is to assess pleural empyema management in our institute, to establish an ICP and to review the impact of this on the patient journey. Data were collected about management strategies, pain control and length of hospital stay from children admitted in 2000 with a diagnosis of pleural empyema. An integrated care pathway was developed to facilitate change in practice and provide greater consistency in management. This incorporated the use of intrapleural urokinase and guidelines on pain control. This was followed by data collection in 2004 to review the impact of the integrated care pathway. The 2000 review revealed that the majority of children (eight of 13) underwent a primary surgical intervention. Urokinase was not used. The median length of stay was 11.5 days (range 4–49 days). Implementation of the pathway led to a reduction in the number of children who underwent surgery (one of 18) with no adverse impact on clinical outcome. Median length of stay was 9 days (range 2–28 days). Children had a smoother patient journey, with prompter investigation and intervention. Children on the pathway had smaller chest drains inserted, received urokinase and had a clearly recorded analgesia strategy. Pleural empyema in childhood requires multi-disciplinary management. The implementation of an integrated care pathway is a valuable tool for managing a condition that requires multi-disciplinary input.
Keywords: Integrated care pathway; pleural empyema; intrapleural urokinase